A bill to nationalise the mines and minerals of the United Kingdom and to provide for the national winning, distribution and sale of coal and other minerals (Co-operative Printing Society, 1919)
Probably a draft of : The natinalisation of mines and minerals bill, 1919 : a bill to nationalise the mines ...